1997
DOI: 10.2307/2411203
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Population Genetic Structure in Tropical Pacific Sea Urchins

Abstract: Unlike populations of many terrestrial species, marine populations often are not separated by obvious, permanent barriers to gene flow. When species have high dispersal potential and few barriers to gene flow, allopatric divergence is slow. Nevertheless, many marine species are of recent origin, even in taxa with high dispersal potential. To understand the relationship between genetic structure and recent species formation in high dispersal taxa, we examined population genetic structure among four species of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(95 citation statements)
references
References 26 publications
4
91
0
Order By: Relevance
“…Indeed, similar patterns of genetic differentiation were identified in two amphidromous species, the gastropod Neritina canalis (Crandall et al 2010) and the fish Sicyopterus lagocephalus (Lord et al 2012). Likewise, a sharp genetic break has been found between the Central and Western Pacific populations within the sea urchin species Echinometra mathaei and E. oblonga (Palumbi et al 1997), the coral reef fishes Acanthurus triostegus (Planes and Fauvelot 2002) and Scarus psittacus (Winters et al 2010), and the snapper fishes Lutjanus kasmira and L. fluvus (Gaither et al 2010). The biogeographic genetic break has commonly been explained by a combination of parameters, such as past changes in climate and water mass circulation and random long-distance dispersal events (e.g., Palumbi et al 1997;Planes and Fauvelot 2002;Lord et al 2012).…”
Section: Isolation Of Peripheral Geographic Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, similar patterns of genetic differentiation were identified in two amphidromous species, the gastropod Neritina canalis (Crandall et al 2010) and the fish Sicyopterus lagocephalus (Lord et al 2012). Likewise, a sharp genetic break has been found between the Central and Western Pacific populations within the sea urchin species Echinometra mathaei and E. oblonga (Palumbi et al 1997), the coral reef fishes Acanthurus triostegus (Planes and Fauvelot 2002) and Scarus psittacus (Winters et al 2010), and the snapper fishes Lutjanus kasmira and L. fluvus (Gaither et al 2010). The biogeographic genetic break has commonly been explained by a combination of parameters, such as past changes in climate and water mass circulation and random long-distance dispersal events (e.g., Palumbi et al 1997;Planes and Fauvelot 2002;Lord et al 2012).…”
Section: Isolation Of Peripheral Geographic Locationsmentioning
confidence: 99%
“…Therefore, Indo-Pacific species that occur up to the Central Pacific are generally thought to have colonized eastern remote islands through a stepping-stone pattern of dispersal. Accordingly, genetic studies of widely distributed marine and freshwater species have demonstrated genetic divergences between Western and Central Pacific populations associated with patterns of isolation by distances (e.g., Palumbi et al 1997;Planes and Fauvelot 2002;Crandall et al 2010;Gaither et al 2010;Winters et al 2010;Lord et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, gene flow in marine species can be constrained by dispersal barriers, such as narrow water passages between land masses, sharp salinity gradients or different types of currents e.g., circular currents (eddies) or downward currents. As marine barriers are not always easily identified, they might lead to population structure even in high dispersal species (Quesada et al 1995;Palumbi et al 1997). …”
Section: Introductionmentioning
confidence: 99%
“…As in other Echinometra, Ec and Eo are sympatric but hybrids are rare or absent (Geyer and Palumbi, 2005). The only evidence of hybridization in the field is a single specimen out of 97 examined that had similar color and spicules characteristics of Em, but with the mtDNA of Eo (Palumbi et al, 1997). This specimen may have represented a backcross, perhaps of several generations (Rahman et al, 2004a).…”
Section: Discussionmentioning
confidence: 88%